(3eUHGM GdYdhe aj eYQaI GdMi Gdbjhes - (3CHh GdMSf CMeO Hf GdMSjf Hf eMeO Hf CHj HcQ GdQUGU GdUfYGfjs
(3ChdgG (B:s
(3CYde Cf GdPi jLH Ydi Gdecda Cf jYQa Gddg JYGdi hJhMjOg hYOdg hUOb hYOg hhYjOg hgPg GdLedI JTJed Ydi KdGKI aUhd s
(3BNQgG (B:s
(3ChdFc GdPjf gOGge Gddg , hChdFc ge ChdhG GdCdHGH Je hGdMeO ddg hMOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds